From Cradle to Plate: Analysing the Life Cycle Sustainability of Fish Feed Composition - Zlaugotne Beate; Pubule Jelena (Environmental and Climate Technologies)
Sustainability is defined as balancing environmental, economic and social factors, and various methodologies and tools are available to assess sustainability across sectors and scales. The demand for food has increased due to the increase in the population and the consumption of aquatic food in the world has increased significantly and is growing by an average of 3 % per year, while the population is growing by 1.6 % per year. As the aquaculture industry expands worldwide, it is important to consider the environmental impact of the industry and choose environmentally friendly alternatives to reduce its impact. The aim of this study is to assess the composition of five different fish feeds based on environmental, economic and social parameters using life cycle analysis (LCA), life cycle costing (LCC), social life cycle analysis (S-LCA) as well as technical considerations. The impact of alternatives to the main feed ingredients was analysed separately, while the development of fish feed focused on the protein source used in the feed and the oil used, as halieutic resources are used as raw material in their production, and alternatives are being considered. The best alternatives, considering all four dimensions, were the alternatives where fishmeal protein was partially replaced by Black Solder fly and Yellow Mealworm protein, as the proportion replaced is different for each alternative. By evaluating fish feed along several dimensions, the aim is to improve fish welfare while reducing the environmental impact of feed production.